Intercomparison of O 3 profiles observed by SCIAMACHY and ground based microwave instruments - Palm, M.; V. Savigny, C.; Warneke, T.; Velazco, V.; Notholt, J.; Künzi, K.; Burrows, J.; Schrems, O. (CCSD, 2005)
International audience Ozone profiles retrieved from limb scattering measurements of the SCIAMACHY instrument based on the satellite ENVISAT are compared to ground-based low altitude resolution remote sensors. All profiles are retrieved using optimal estimation. Following the work of Rodgers and Connor (2003) the retrievals of the ground-based instruments are simulated using the SCIAMACHY retrieval. The SCIAMACHY results and the results of the ground-based microwave radiometer in Bremen and Ny Ålesund agree within the expected covariance of the intercomparison.